Dermoscopic features and screening strategies for the detection of small‐diameter melanomas. (15th February 2022) - Regio Pereira, Amanda; Corral‐Forteza, Marina; Collgros, Helena; El Sharouni, Mary‐Ann; Ferguson, Peter M.; Scolyer, Richard A.; Guitera, Pascale
Summary: Background: Around 70% of cutaneous malignant melanomas (MMs) develop de novo, and small‐diameter or 'tiny' lesions are expected to represent the earliest manifestation of most MMs. Aim: To describe the clinical, histopathological and dermoscopic features of tiny MMs, and to investigate the impact of imaging tools, including total body photography (TBP) and sequential digital dermoscopy imaging (SDDI) in their detection. Methods: Consecutive MMs diagnosed over 2 years in a referral centre were retrospectively included. Tiny MMs were defined as MMs with a diameter of ≤ 5 mm on dermoscopy. Dermoscopic features and the performance of four imaging methods were evaluated. Results: Of the 312 MMs included, 86 (27.6%) measured ≤ 5 mm, and 44.2% of these were invasive. Tiny MMs were more frequently excised for being new and/or changing compared with nontiny MMs (77.9% vs. 50.9%; P  < 0.001). Half of the tiny MMs would have been missed by the dermoscopic seven‐point checklist (48.2%) or the three‐point checklist (49.4%), while Menzies' method and the revised pattern analysis correctly identified respectively 65.9% and 63.5% of the tiny MMs. The most frequent positive features for tiny MMs were asymmetry in structure or colour (77.6%), brown dots (65.9%), irregular dots and globules (76.5%) and atypical pigment network (44.7%). Dermoscopic features predictive of invasion in tiny MMs were atypical vascular pattern (OR = 26.5, 95% CI 1.5–475.5, P  < 0.01), shiny white lines (OR = 12.4, 95% CI 0.7–237.8, P  = 0.04) and grey/blue structures (OR = 3.7, 95% CI 1.3–10.5, P  = 0.01). Conclusion: Tiny MMs are frequently invasive and represent a clinical, dermoscopic and histopathological challenge. Dermoscopy alone has suboptimal diagnostic accuracy. Early diagnosis relies on the detection of new or changing lesions aided by TBP and SDDI. Abstract : Small‐diameter melanomas are frequently invasive and represent a clinical, dermoscopic and histopathological diagnostic challenge. Most small‐diameter melanomas were detected for being a new or changing lesion and dermoscopy alone has suboptimal diagnostic accuracy. The most frequent positive dermoscopic features for small‐diameter melanomas are asymmetry in structure or colour, brown dots, irregular dots and globules and atypical pigment network. Atypical vascular pattern, shiny white lines and grey/blue structures on dermoscopy were associated with invasiveness and should prompt excision.